Blending sludge alkaline hydrolysate and urea affects grape yield and quality by regulating soil bacterial communities - Xue, Donghe; Yang, Yan; Zhang, Huofeng; Quan, Yijie; Li, Zejin; Li, Zixu; Wang, Wei; Bo, Huijuan; Jin, Dongsheng; Xu, Minggang; Zhang, Qiang; Yang, Zhiping (Frontiers in Plant Science, 2025)
IntroductionFertilization is vital for improving grape (Vitis vinifera L.) yield and quality. Unlike traditional nitrogen fertilizers, the mechanisms by which sludge alkaline hydrolysate (SAH), a novel fertilizer, influences grape quality and yield are still poorly understood.MethodsIn this study, six treatments were established: 20% SAH + 80% urea (M1), 40% SAH + 60% urea (M2), 60% SAH + 40% urea (M3), 80% SAH + 20% urea (M4), pure SAH (M5), and pure urea (M6). The effects of applying SAH and urea mixtures to grapes were evaluated, with focus on performance parameters, soil nutrients, and microbial communities.Results and discussionThe results show that 60–80% SAH application significantly enhanced grape stem thickness, chlorophyll content, photosynthetic efficiency, fruit quality, and increased yield. Concurrently, it elevated soil nutrient contents, improved microbial community structure, and altered nitrogen cycle gene copy numbers. Molecular ecological network analyses indicated that Firmicutes, Acidobacteriota, Gemmatimonadota, and Ascomycota were key taxa. Bacterial–fungal cooperation was the dominant interaction, accounting for 65.98–94.61% of all observed microbial interactions, compared to antagonistic interactions. Mantel analysis showed that bacterial community and nitrogen cycle genes (ammonia-oxidizing bacteria (AOB), nitrogen fixation hydrogenase (nifH)) were important for grape yield and quality. These findings offer guidance for the effective use of SAH in grape production. Future studies should elucidate how SAH regulates fruit quality-related gene expression to uncover its mechanisms and enable its full-scale use in viticulture.